Pengembangan Media Puzzle Mufrodat untuk Meningkatkan Keterampilan Berbicara pada Mata Pelajaran Bahasa Arab Kelas 1 - Choerul Anwar Badruttamam; Dwi Rosyidatul Kholidah; Khofifah (IBTIDA', 2021)
The purpose of this media development is to producemedia product puzzle afun mufrodatthat is used in learning Arabic for grade 1, especially in the material, .بيتي so that it can make active learning, increase Arabic vocabulary mastery, andimprove speaking skills in vocabulary pronunciation. This type of research is a research and development (Researchand Development/R & D), which refers to the ADDIE models, with specs include 5 stages of media development are: 1). Analysis, 2). Design, 3). Development, 4). Implementation, 5). Evaluation. The form of research used by researchers isdescriptive with quantitative and qualitative data analysis. The results of research and development ofmedia puzzle mufrodat indicate that media is puzzle mufrodatappropriate to be used as a medium for learning Arabic for grade 1 to improve speaking skills. This can be seen from the results of validation by several experts and field trials that reached very valid criteria. The results of the validation test of material experts reached a 95% feasibility level, linguists reached 92% and media experts reached 93.8%. The results of the studentresponse questionnaire reached 97.8%. Based on the results of the multiple choicetask, an average score of 85 was obtained, the matching task obtained an averagescore of 84.5 and the task in the form of an oral test mentioning mufrodat obtainedan average score of 96.